2017
DOI: 10.1155/2017/7659893
|View full text |Cite
|
Sign up to set email alerts
|

ArmAssist Robotic System versus Matched Conventional Therapy for Poststroke Upper Limb Rehabilitation: A Randomized Clinical Trial

Abstract: The ArmAssist is a simple low-cost robotic system for upper limb motor training that combines known benefits of repetitive task-oriented training, greater intensity of practice, and less dependence on therapist assistance. The aim of this preliminary study was to compare the efficacy of ArmAssist (AA) robotic training against matched conventional arm training in subacute stroke subjects with moderate-to-severe upper limb impairment. Twenty-six subjects were enrolled within 3 months of stroke and randomly assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 28 publications
0
40
0
1
Order By: Relevance
“…The AA system has been previously tested in clinical setting by therapists and patients with positive results on acceptance (11) and effectiveness with the improvements in the motor function of the patients after the use of it (24). Previous studies also demonstrated that the therapy using AA system is enjoyable and motivating because engages patients (27).…”
Section: The Merlin Robotic-assisted Telerehabilitation Systemmentioning
confidence: 99%
“…The AA system has been previously tested in clinical setting by therapists and patients with positive results on acceptance (11) and effectiveness with the improvements in the motor function of the patients after the use of it (24). Previous studies also demonstrated that the therapy using AA system is enjoyable and motivating because engages patients (27).…”
Section: The Merlin Robotic-assisted Telerehabilitation Systemmentioning
confidence: 99%
“…It is also considered one of the main causes of disabilities [15], resulting not only in persistent neurological deficits but also in upper limb dysfunction, which affects about 85% of stroke survivors, and less than half recover motor function within three months of poststroke. In addition, the level of recovery of the motor function has a great influence on the participation of people in community environments and on the quality of life [1].…”
Section: Post-stroke Rehabilitationmentioning
confidence: 99%
“…Rehabilitation programs generally focus on tasks with a large number of repetitions, which is essential for promoting motor learning [16] and it is positively related to better motor recovery [1,17]. However, conventional treatments are not as frequent and intense as required because of the cost and of the commitment of patients in rehabilitation programs that eventually become repetitive.…”
Section: Post-stroke Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Aún así, algunos autores han seguido investigando por esta linea, siendo muchos los robots serie de rehabilitación que se pueden encontrar en la bibliografía, como es el caso de los robots WAM (Whole Arm Manipulator) (Bai et al, 2017;Rainer Birkenbach et al, 2012), ATD (Active therapeutic device) (Westerveld et al, 2014) o Robotherapist (Furusho et al, 2007). Los avances de las propuestas han permitido realizar los primeros ensayos con pacientes con discapacidad motora comprobando los beneficios de terapias de neurorehabilitación a través de dispositivos robóticos (Tomić et al, 2017;Lledó et al, 2016).…”
Section: Introductionunclassified